The effect of rainrate modeling for the prediction of satellite propagation in Malaysia - Alwarfalli, Ayman A. A. (2005)
By increasing number of commercial applications are being promoted for future satellites broadband services, the appearance of such systems with due to its growing demand for radio frequency spectrums. Since lower frequencies have become saturated, a transition to higher frequencies band such as Ka-band (20/30 GHz) and above has become necessary. These bands are attractive because it offers wider bandwidth, higher data rates and smaller component sizes. On the other hand, higher frequencies have more propagation problems. Attenuation caused by rain is major limitation can be a serious problem especially in the tropical regions. In Malaysia, the tropical climate effects study for higher frequency band become increasingly important. The main concern of this project is therefore, to study and analyze the measured field data of the rain attenuation within these bands. To achieve this, previous researchers measured field data are studied and analyzed to understand the behavior of signal propagation during rainfall event, particularly for Malaysia. To achieve this goal, various experiments were conducted using microwave links, satellite broadcasting receiver and rain gauges. An overview of published and proposed prediction model of rain attenuation on satellite link is discussed based on this data, the latest developments in prediction and modeling techniques presented and discussed. Moreover, a proposed prediction model of rain attenuation in Malaysia is employed and tested, in order to determine the rain attenuation of slant and terrestrial path. The project goals are extended to an adaptive prediction model of the specific attenuation, rain height and effective horizontal length. With the verifications of the proposed model using ITU-R (Study Group3), it is possible to improve the efficiency of satellite communication in Malaysia with an improved design for future broadband and multimedia satellite.